2023
DOI: 10.1073/pnas.2307149120
|View full text |Cite
|
Sign up to set email alerts
|

A robust, agnostic molecular biosignature based on machine learning

H. James Cleaves,
Grethe Hystad,
Anirudh Prabhu
et al.

Abstract: The search for definitive biosignatures—unambiguous markers of past or present life—is a central goal of paleobiology and astrobiology. We used pyrolysis–gas chromatography coupled to mass spectrometry to analyze chemically disparate samples, including living cells, geologically processed fossil organic material, carbon-rich meteorites, and laboratory-synthesized organic compounds and mixtures. Data from each sample were employed as training and test subsets for machine-learning methods, which resulted in a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Determining the signatures of life is challenging because we have no universal definition of life, we only have the example of life as we find it on Earth (Barge et al 2022;Bartlett & Wong 2020;Chou et al 2021aChou et al , 2021bCleland 2019aCleland , 2019bGuttenberg et al 2021;Johnson et al 2018;Marshall et al 2021). However, recent work has demonstrated that general measures of molecular complexity exhibit strong associations with "biogenicity" and hence could be used as agnostic chemical biosignatures (Cleaves et al 2023;Guttenberg et al 2021;Marshall et al 2021). At the planetary scale, entropy-based measures of transit spectra have also been proposed as a way to quantify the similarity of a given exoplanet atmosphere to that of Earth (Vannah et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Determining the signatures of life is challenging because we have no universal definition of life, we only have the example of life as we find it on Earth (Barge et al 2022;Bartlett & Wong 2020;Chou et al 2021aChou et al , 2021bCleland 2019aCleland , 2019bGuttenberg et al 2021;Johnson et al 2018;Marshall et al 2021). However, recent work has demonstrated that general measures of molecular complexity exhibit strong associations with "biogenicity" and hence could be used as agnostic chemical biosignatures (Cleaves et al 2023;Guttenberg et al 2021;Marshall et al 2021). At the planetary scale, entropy-based measures of transit spectra have also been proposed as a way to quantify the similarity of a given exoplanet atmosphere to that of Earth (Vannah et al 2023).…”
Section: Introductionmentioning
confidence: 99%